Brazilian version of the body dysmorphic disorder examination - Jorge, Renata Trajano Borges (2008)
CONTEXT AND OBJECTIVE: Body image improvement is considered to be the main reason for undergoing plastic surgery. The objective was to translate the body dysmorphic disorder examination (BDDE) into Brazilian Portuguese and to adapt and validate this questionnaire for use in Brazil. DESIGN AND SETTING: Cross-sectional survey, at the Department of Plastic Surgery of Universidade Federal de São Paulo. METHODS: The BDDE was fi rst translated into Portuguese and then back-translated into English. These translations were then discussed by healthcare professionals in order to establish the fi nal Brazilian version. In a second stage, the validity and reliability of the BDDE were assessed. For this, patients were initially interviewed by two interviewers and subsequently, by only one of these interviewers. On the fi rst occasion, in addition to the BDDE, the body shape questionnaire (BSQ) and the Rosenberg self-esteem scale were also applied. These questionnaires were applied to 90 patients. RESULTS: Six questions were modifi ed during the assessment of cultural equivalence. Cronbach’s alpha was 0.89 and the intraclass correlation coeffi cients for interobserver and test-retest reliability were 0.91 and 0.87, respectively. Pearson’s coeffi cient showed no correlation between the BDDE and the Rosenberg self-esteem scale (0.22), whereas there was a moderate correlation between the BDDE and the BSQ (0.64). CONCLUSIONS: The BDDE was successfully translated and adapted, with good internal consistency, reliability and construct validity.